Linkage analysis of two cloned DNA sequences, DXS197 and DXS207, in hypophosphatemic rickets families. - Thakker, R; Davies, K; Read, A; Tippett, P; Wooding, C; Flint, T; Wood, S; Kruse, T; Whyte, M; O'Riordan, J (1990)
The human X-linked hypophosphatemic rickets gene locus (HYP, formerly HPDR) has been previously localized by linkage analysis to Xp22.31-Xp21.3 and the locus order Xpter-DXS43-HYP-DXS41-Xcen established. Recombination between HYP and these flanking markers is frequently observed and additional markers have been sought. The polymorphic loci DXS197 and DXS207 have been localized to Xpter-Xp11 and Xp22-Xp21, respectively. We have further localized DXS197 to Xpter-Xp21.3 by using a panel of rodent-human hybrid cells and have established the map positions of DXS197 and DXS207 in relation to HYP by linkage studies of hypophosphatemic rickets families. Linkage between DXS197 and the loci DXS43, DXS85, and DXS207 was established with peak lod score values of 6.19, 0 = 0.032; 4.14, 0 = 0.000; and 3.01, 0 = 0.000, respectively. Multilocus linkage analysis mapped the DXS197 and DXS207 loci distal to HYP and demonstrated the locus order Xpter-DXS85-(DXS207, DXS43, DXS197)-HYP-DXS41-Xcen. These additional genetic markers DXS197 and DXS207 will be useful as alternative markers in the genetic counseling of some families.